Nimotuzumab Combined With Irradiation Enhances the Inhibition to the HPV16 E6-Promoted Growth of Cervical Squamous Cell Carcinoma - Xu, Zhonghua; Shu, Hang; Zhang, Fan; Luo, Weiwei; Li, Yan; Chu, Jinjin; Zhao, Qihong; Lv, Yin (Frontiers in Oncology, 2020)
Human papillomavirus (HPV) 16 E6 has been proved to increase the radiosensitivity and lead to the EGFR overexpression in cervical cancer cells. In this study, to investigate the inhibition of nimotuzumab-mediated EGFR blockade combined with radiotherapy, we established a C33A cervical squamous cell line overexpressed HPV16-E6 and a nude mouse model bearing these cell lines. The CCK-8 assay was used to detect the effects of various treatments on the proliferation of C33A cells. Flow cytometry was used to detect the rates of apoptosis and cell cycle arrest. Gene transcription and protein expression were detected by quantitative real-time polymerase chain reaction (qRT-PCR) and western blot, respectively. Immunohistochemical staining was used to evaluate protein expression in tumor tissue. We revealed that E6-overexpressing C33A cells grew faster and were more sensitive to radiotherapy than control cells in vitro and in vivo. The expression levels of EGFR, as well as those of downstream signaling molecules AKT and ERK 1/2, were significantly upregulated in C33A cells that overexpressed E6. We observed that nimotuzumab combined with radiotherapy could enhance the inhibition of C33A cell growth induced by E6, both in vitro and in vivo. We also observed enhanced effect after combination on G2/M cell cycle arrest and apoptosis in E6-overexpressing C33A cells. Furthermore, the combined therapy of nimotuzumab and radiation remarkably reduced the protein expression levels of EGFR, AKT, ERK 1/2 in vitro and in vivo. In conclusion, HPV16 E6 expression is positively correlated with levels of EGFR, AKT, and ERK 1/2 protein expression. The combined treatment with nimotuzumab and radiotherapy to enhance radiosensitivity in E6-positive cervical squamous cell carcinoma was related to enhanced G2/M cell cycle arrest and caspase-related apoptosis.